The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1089/g4h.2012.0013
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Perceptions of a Game About Warfarin and Vitamin K: A Pilot Study

Abstract: The findings suggest that patients were satisfied with the game, which indicates that adult patients on warfarin are open to game use as an educational tool to learn health information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Within health care, serious games have been developed for educating both patients and health care professionals. For example, serious games have been tested with the goals of (1) improving patients’ self-care for diabetes, asthma, cancer, and Warfarin use and (2) improving diet, pain, mobility, lifestyle, and health-related knowledge [ 3 , 6 - 9 ]. Within this field, a recent study reported a successful validation of a framework that gamifies self-management of diabetes and its acceptance by patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Within health care, serious games have been developed for educating both patients and health care professionals. For example, serious games have been tested with the goals of (1) improving patients’ self-care for diabetes, asthma, cancer, and Warfarin use and (2) improving diet, pain, mobility, lifestyle, and health-related knowledge [ 3 , 6 - 9 ]. Within this field, a recent study reported a successful validation of a framework that gamifies self-management of diabetes and its acceptance by patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of serious games in healthcare has been tested with the goal of improving self--care in diabetes, asthma, cancer and Warfarin use, improving diet, pain, mobility, lifestyle and other behavioural changes, as well as health--related knowledge. [14][15][16][17]72 Although inconclusive as yet, many studies have reported positive outcomes. However, methodological problems and differences in learning goals and definitions of outcomes call for larger studies and randomized controlled trials to test the effect on knowledge and self--care behaviour in this new field within patient education.…”
Section: Serious Gamesmentioning
confidence: 99%